2010
DOI: 10.1155/2010/910636
|View full text |Cite
|
Sign up to set email alerts
|

Propylthiouracil-Induced Acute Liver Failure: Role of Liver Transplantation

Abstract: Propylthiouracil- (PTU-) induced hepatotoxicity is rare but potentially lethal with a spectrum of liver injury ranging from asymptomatic elevation of transaminases to fulminant hepatic failure and death. We describe two cases of acute hepatic failure due to PTU that required liver transplantation. Differences in the clinical presentation, histological characteristics, and posttransplant management are described as well as alternative therapeutic options. Frequent monitoring for PTU-induced hepatic dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 20 publications
4
21
0
3
Order By: Relevance
“…Various mechanisms have been proposed including inhibition of glucoronyl transferase, reduced bile acid synthesis and increased oxygen consumption by hepatocytes [5][6][7]. Liver biopsy and postmortem examinations have revealed various degrees of inflammation and liver necrosis.…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Various mechanisms have been proposed including inhibition of glucoronyl transferase, reduced bile acid synthesis and increased oxygen consumption by hepatocytes [5][6][7]. Liver biopsy and postmortem examinations have revealed various degrees of inflammation and liver necrosis.…”
Section: Mechanismmentioning
confidence: 99%
“…Liver transplantation was required for some patients with fulminant hepatic failure [3][4][5]29]. One pregnant patient received a successful liver transplant but had fetal death [30].…”
Section: Managementmentioning
confidence: 99%
“…15 While much less common, there have been rare case reports of acute hepatic failure and death from methimazole. 16 Patients who previously had neomercazole induced hepatitis should not be rechallenged as there is a high risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…11,13 On the other hand, clinicians advised frequent monitoring of liver function in PTU-treated patients. 11,13,17,[40][41][42][43][44] Hence, finding the mechanism(s) of PTU-induced hepatotoxicity might help to prevent or cure liver injury induced by this drug. Previously, we found that PTU-induced liver injury was associated with oxidative stress and its associated complications in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Several cases of PTU-induced hepatotoxicity have been reported. 4,[11][12][13][14][15][16] Pediatrics seems to be more vulnerable to PTU-induced hepatotoxicity. 17 There is no precise mechanism for PTU-induced liver injury.…”
Section: Introductionmentioning
confidence: 99%